Alkaline magmatism in the Paraná Basin: A comparative study. II. Geochronology and geochemistry - Gomes, Celso de Barros (Geochimica Brasiliensis, 2025)
Radiometric data demonstrate the age variability of alkaline magmatic events that affected the Paraná Basin. The oldest event, dated to the Middle Triassic (241 Ma), took place in border areas between Brazil and Paraguay. Four distinct episodes are distinguished in the Early Cretaceous. The earliest of these (139 Ma) predates the emplacement of the tholeiitic lava flows of the Serra Geral group. It is followed by a post-tholeiitic episode (126 Ma) containing the largest number of alkaline occurrences in Eastern Paraguay. A late Early Cretaceous event (118 Ma) is exclusive to the southeastern portion of the territory. A brief episode (110-100Ma) is associated to the Ponta Grossa arch. The Late Cretaceous episode (90–70 Ma), not recorded in Paraguay, is compositionally diverse and particularly widespread in Brazilian areas of the basin, with a minor occurrence in Bolivia (Candelaria). Paleogene alkaline rocks primarily forming small dikes and plugs (59 Ma) represent the youngest alkaline expressions, found in both Brazilian and Paraguayan domains. The alkaline magmatism ranges in composition from ultrabasic to acid, prevailing evolved intrusive silica-undersaturated to silica-saturated types of potassic nature and variable K/Na ratios. The geochemical characteristics of the associated petrographic assemblages are described for each alkaline province, and general considerations are presented regarding the genesis of the alkaline magmatism.